Значение лесных муравьев голоспинных как энтомофагов в дубовых насаждениях - Гримальский, В.И.; Лозинский, В.А. (Вестник зоологии, 1967)
Some cases are registrated when with a great number of nests of Formica polyctena Forst. (up to 7,5 per 1 hectare at an average) in mixed pine-oak plantations, the leaf-eating vermin ate the oak leaves very often but at the same time they did not eat the pine needle. It is find out that leaf-eating insects damage most of all those trees which are rarely visited by ants. But a regular connection (on which M. S. Malysheva had reported in 1963) is not established between the number of aphisides on the oak on one hand and visitation of an oak by ants and mass reproduction of leaf-eating vermin — on the other hand. In the active seat of Tortrix viridana L. the Formica polyctena Forst. protected against the vermin 6-20% of trees. The ants ate the caterpillar of Operophtera brumata L. and Erannis defoliaria C 1. more actively than the catepillar of Torrtrix viridana L